Efforts to Increase Knowledge of Clean and Healthy Living Behaviors (PHBS) Through Counseling and Making Hand Sanitizers at 152 Gresik State Elementary Schools - Oky Istiowati; Yunita Rizkia Pratiwi; Afdhol Mufassirin; Dina Anggraeni Susesti; Viera Nuriza Pratiwi (Journal of Health Community Service, 2023)
PHBS in schools is the implementation of certain health procedures by empowering teachers, students, and the community in the school environment. Based on the results of the survey that has been conducted by the research team at the 152 Gresik State Elementary School , there are several students who are experiencing hygiene problems, namely 45 (73%) of the 69 students and almost all students experience it. The purpose of this activity is to reduce the incidence of hygiene problems with health counseling about PHBS and the manufacture of natural hand sanitizers in elementary schools, so as to reduce the number of hygiene problems. The method used in this activity was descriptive through a survey approach conducted on 69 students, the presentation of material about PHBS in reducing student hygiene problems. As a result of the activities that have been carried out by the research team after the presentation of the material and the making of hand sanitizers in the elementary school, the incidence of hygiene problems decreased to 25 students (36%) who experienced hygiene problems. The manufacture of hand sanitizers is very influential in carrying out the health program that has been prepared by the research team.